1995
DOI: 10.1002/j.1460-2075.1995.tb00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin receptors, erbB3 and erbB4, are localized at neuromuscular synapses.

Abstract: Neuregulin (NRG) is concentrated at synaptic sites and stimulates expression of acetylcholine receptor (AChR) genes in muscle cells grown in cell culture. These results raise the possibility that NRG is a synaptic signal that activates AChR gene expression in synaptic nuclei. Stimulation of NRG receptors, erbB3 and erbB4 initiates oligomerization between these receptors or between these receptors and other members of the epidermal growth factor (EGF) receptor family, resulting in stimulation of their associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(117 citation statements)
references
References 30 publications
3
113
1
Order By: Relevance
“…Consistent with other investigators, we have demonstrated the expression and localization of ErbB2, ErbB3, and ErbB4 proteins in skeletal muscle and the enrichment of these receptors at the NMJ (2,14,15,25,40,48). A novel finding in our study is the increased expression of ErbB3 in the EDL, a predominantly fasttwitch, glycolytic muscle compared with the soleus, a predominantly slow-twitch, oxidative muscle.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other investigators, we have demonstrated the expression and localization of ErbB2, ErbB3, and ErbB4 proteins in skeletal muscle and the enrichment of these receptors at the NMJ (2,14,15,25,40,48). A novel finding in our study is the increased expression of ErbB3 in the EDL, a predominantly fasttwitch, glycolytic muscle compared with the soleus, a predominantly slow-twitch, oxidative muscle.…”
Section: Discussionsupporting
confidence: 92%
“…Frozen sections (10 µm) from fixed, adult leg muscles were stained with antibodies as described previously (DeChiara et al, 1996;Zhu et al, 1995). The following primary antibodies were used: affinitypurified rabbit anti-rapsyn (1:500) (Herbst and Burden, 2000), mouse anti-utrophin C terminus (1:20, Vector Labs), rabbit anti-Na + channel (1:1000, Upstate), rabbit anti-ErbB4 (antibody # 616) (Zhu et al, 1995), rabbit anti-synaptophysin (1:20, Zymed), mouse anti-SV2 (1:10) (Buckley and Kelly, 1985) and rabbit anti-Musk (#83033, 1:4000 and #24908, 1:50) (Watty et al, 2000).…”
Section: Mouse Genotypingmentioning
confidence: 99%
“…The following primary antibodies were used: affinitypurified rabbit anti-rapsyn (1:500) (Herbst and Burden, 2000), mouse anti-utrophin C terminus (1:20, Vector Labs), rabbit anti-Na + channel (1:1000, Upstate), rabbit anti-ErbB4 (antibody # 616) (Zhu et al, 1995), rabbit anti-synaptophysin (1:20, Zymed), mouse anti-SV2 (1:10) (Buckley and Kelly, 1985) and rabbit anti-Musk (#83033, 1:4000 and #24908, 1:50) (Watty et al, 2000). We were unable to detect fluorescence from the Musk-GFP transgene.…”
Section: Mouse Genotypingmentioning
confidence: 99%
“…For example, the common transmembrane topology of mesenchymal isoforms, which is not shared by most neuronal factors, may enhance binding and increase availability of the lower a nity ligands. This proposition is supported by the apparent short range of NDF/neuregulin action in vivo, including its involvement in cardiac development (Gassmann et al, 1995;Lee et al, 1995;Meyer and Birchmeier, 1995), contact-induced mitosis of Schwann cells by neuron-expressed neuregulins (Morrissey et al, 1995), co-localization of neuregulin and its receptors in the neuromuscular synapse (Zhu et al, 1995), and mesenchyme-epithelia interaction during mammary gland development (Yang et al, 1995).…”
Section: Distinct Expression Features Of the Two Ndf Receptorsmentioning
confidence: 98%